Environmental Oriented Problem-Based Learning (PBL) Improves Learning Outcomes and Self-Efficacy of Students In Social Studies In Fifth-Grade Elementary Schools - Arisanti, Dewa Ayu Kade; Dantes, Nyoman; Suastika, I Nengah (Journal for Lesson and Learning Studies, 2022)
The lack of teacher abilities and skills in varying the application of learning models impacts low learning outcomes and student self-efficacy in social studies subjects in grade V. This study aims to produce a product in the form of an environment-oriented problem-based learning model. This research belongs to the type of development research that was developed using the 4D model. The 4D model consists of four research stages: defining, designing, developing, and deploying. The subjects involved in this study were social studies learning experts, expert practitioners of 15 high-grade teachers, and 51 fifth-grade elementary school students. Data collection in the study was carried out using non-test and test methods, with research instruments in the form of questionnaires and multiple-choice tests. The data obtained in the study were then analyzed using a feasibility test with validity and product trials. The research analysis results show that the learning model developed gets an average score of 4.9 in the "very good" category. Furthermore, the results of testing the simultaneous effect of environment-oriented problem-based learning models on student learning outcomes and self-efficacy show an influence on the dependent variable (social studies learning outcomes and self-efficacy). Based on these results, the environment-oriented problem-based learning model has very good qualifications, so it is feasible to be applied in the social studies learning process for fifth-grade elementary school students.